Security Issues in a Changing Asian Region - Tuychiyeva, Rano (Security Issues in a Changing Asian Region, 2021)
The book entitled “Security Issues in a Changing Asian Region,” describes the geopolitical architecture of the Asian region from the late twentieth century to the 2020. It analyzes in detail the main sources of threats to peace and security in the region, as well as political, social and security factors that hinder regional development and the strengthening of interregional relations. The role of the socio-political situation in India in the formation of the geopolitical map of the Asian region, the country's foreign policy principles, participation in regional security and activities within regional cooperation organizations are also central to this study. A review of Asian security shows that security concerns have spread throughout Asia. At the same time, such problems also have a significant negative impact on mutual economic, trade and investment relations. New Delhi sees inter-regional existing and planned relations as promising tasks. Mutual economic interests will help maintain control over political conflicts, at least for the foreseeable future. India has enormous potential and if the current government achieves this, it can assume the role of a strategic player in the Asian region.